ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJADWALAN DAN MANAJEMEN TRAINING PADA SOFTWARE LABORATORY CENTER UNIVERSITAS BINA NUSANTARA - Meiliana - (Jurnal Sistem Informasi, 2014)
Human resource management is considered as a contemporary development that continues to reshape employees’ competence. As one of educational services unit in BINUS UNIVERSITY that specifically provides software-based practical work for students, Software Laboratory Center (SLC) is regularly conducted a training program every term as a part of human resource management. There are two main triggers of the regular training program in SLC. First, the rapid development of software-based knowledge that needs to be learned, filter, and adopted to the curriculum. Second, the high turnover of teaching assistants requires a training program to attain a subject teaching qualification for new assistants and to maintain the competence of the current teaching assistants. Along with university operational timeline, training for teaching assistants are manually managed every term by SLC, from collecting transaction data for next term, calculating the estimation of assistant needed, allocating assistants for training, scheduling the training, until evaluating the competence of assistants. Conventional training management system in SLC causes an issue of time efficiencies, validity of assistants’ competence, and risk of human error. Therefore, this paper proposes an analysis and design of scheduling and training management information system with Unified Modeling Language (UML) and data collection. Moreover, we developed a dedicated tool to support the process of training management in SLC. Keywords: Information System, Scheduling, Training System, Web-Based Application.